Comparing Genetic Information of Severe Acute Respiratory Syndrome Corona Virus 2 and SARS CoV and Middle East Respiratory Syndrome Corona Viruses; A Review Study - Niloofar Agharezaee; Flora Forouzesh (Fasa University of Medical Sciences, 2022)
Background & Objective: The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to a global infection and a continuing pandemic. Symptoms have been associated with age, biological sex, and other previous present health situations. The aim of this study was to make a genetic comparison between the SARS-CoV-2, SARS-CoV, and Middle East Respiratory Syndrome (MERS)-CoV using phylogenetic methods. Materials & Methods: In this review study, previously published papers were collected from 2010 to 2020 using electronic sources in reliable databases such as Scopus, PubMed, ISI, Google Scholar, and Science Direct. Then, we performed the bioinformatics study. For sequences alignment, analysis, and phylogenetic construction, all sequences from SARS-CoV-2, SARS-CoV, and MERS-CoV were obtained from the GeneBank database. Results: Eighty percent of SARS-CoV and 50% of MERS-CoV RNA sequences shared with SARS-CoV-2 RNA and SARS-CoV-2 show additional genomic regions. The phylogenetic analysis of the full-length genome sequence shows that SARS-CoV-2 has the highest similarity with SARS-CoV, but it has a lower similarity with MERS-CoV. Considering the close relationship between SARS-2 and SARS, the examination of the amino-corrosive translocation of completely different proteins may prove that there are fundamental and utilitarian differences between SARS-2 and SARS. Conclusion: Although COVID-19 pathogenicity is not well known, MERS-CoV and SARS-CoV pathogenesis still can be the best source of COVID-19 information. The global effect of this new epidemic is yet uncertain. So, analyzing genome sequencing is important for epidemiological, clinical, and experimental studies.